The anatomy of the anterolateral structures of the knee — A histologic and macroscopic approach - Brockmeyer, Matthias; Orth, Patrick; Höfer, Denis; Seil, Romain; Paulsen, Friedrich; Menger, Michael D.; Kohn, Dieter; Tschernig, Thomas (Knee, 2019)
Background: The anatomy of the anterolateral structures of the knee is complex and still controversial. The aim of our study was to analyze this anatomy by histologic and macroscopic evaluation, with a particular emphasis on the anterolateral ligament (ALL). Material and methods: Twenty-three cadaveric knee joints were dissected followed by a qualitative and quantitative anatomic analysis of the anterolateral knee structures. Histology and comparison of different anterolateral structures was performed in addition. Results: The ALL was identified in all of the dissected cadaveric knee specimens. It runs in an oblique course from its proximo-dorsal insertion at the distal femur into a ventro-distal direction to the anterolateral tibia. The femoral insertion site was found to be posterior and slightly proximal to the lateral femoral epicondyle and the femoral attachment of the lateral collateral ligament (LCL). The femoral insertion of the ALL overlapped the LCL in all dissected knees. The tibial insertion site was midway between Gerdy's tubercle (GT) and the tip of the fibular head (FH). In 15 of the dissected 23 knee joints, thin attachments to the lateral meniscus were observed. Histology confirmed differences in the composition of the anterolateral knee joint capsule, the ALL and the iliotibial band (ITB). Conclusions: The ALL occurs as a regular separate anterolateral ligamentous structure. It is distinguishable from the ITB and the anterolateral joint capsule in both embalmed and non-embalmed specimens. Histology of the ALL indicates typical ligamentous tissue which clearly differs from the anterolateral knee joint capsule and the thicker ITB. Level of evidence: Level II, descriptive anatomic study.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Anatomy; Anterior cruciate ligament (ACL); Anterolateral instability; Anterolateral knee structures; Anterolateral ligament (ALL); Histology